The Efforts of The Youth of The Bahung Mosque, Sibatu Batu Village, Sei Dadap Sub-District in Improving the Ability to Write Sermon Texts - Dahmul Dahmul; Ismail Nasution; Abdi Tanjung; Ertugrul Gokcekuyu (STAI Syaichona Moh. Cholil Bangkalan, 2023)
Quantitatively, the number of preachers who preach through writing is much less than preachers who use spoken language. Therefore, this paper focuses on efforts to improve sermon text-writing skills. This paper uses action research, which is one type of qualitative research. This action research examines things that happen in the community or target group, where the results can be directly worn or felt by the community or target group. The result of this research is the achievement of increased skills, as evidenced by the results of the pretest and post-test. Besides that, there are several inhibiting and supporting factors in the efforts of mosque youth to improve sermon writing skills.